Representativity of the genus Asphondylia Loew, 1850 (Diptera, Cecidomyiidae) in Brazil - Flor, Ismael Cividini; Maia, Valéria Cid (Papéis Avulsos de Zoologia, 2017)
Representativity of the genus Asphondylia Loew, 1850 (Diptera, Cecidomyiidae) in Brazil. This cosmopolitan genus includes 272 galling species described, of which about 100 occur in the Neotropical Region. The present study goal to evaluate the richness of Asphondylia in Brazil, to provide an updated list of the host plant species, to determine the plant organs where galls are induced, to update the geographic distribution of the genus, to verify it distribution in the Brazilian biomes, and to the list the associated fauna. The survey data was carried out by consulting the Cecidomyiidae collection of the Museu Nacional/UFRJ, the database “Web of Science” using Asphondylia and Brasil/Brazil as keywords, 51 Brazilian inventories and two catalogues. Asphondylia is represented by 58 species in Brazil, among them, twenty are already known and 38 are still undetermined. The Brazilian described species represent 8% of the total of known species of Asphondylia in the world and 21% of species of the Neotropical fauna. This genus is associated with 51 plant species and 20 plant families in Brazil. Asteraceae comprise the greatest richness of Asphondylia species. This genus was found in five biomes, among them the Atlantic forest has the highest species richness. The associated fauna comprises parasitoids (Hymenoptera) and inquilines (Lepidoptera, Coleoptera and Diptera).